A Conversation on Sexual Rights in India. (CREA, 2005)
Proceedings of the two day Dialogue on Sexual Rights in India held in collaboration of Creating Resources for Empowerment in Action, SANGAMA, and Talking About Reproductive and Sexual Health Issues, Indian organizations.